2013
DOI: 10.1002/jbmr.1879
|View full text |Cite
|
Sign up to set email alerts
|

Variation in tibial functionality and fracture susceptibility among healthy, young adults arises from the acquisition of biologically distinct sets of traits

Abstract: Physiological systems like bone respond to many genetic and environmental factors by adjusting traits in a highly coordinated, compensatory manner to establish organ-level function. To be mechanically functional, a bone should be sufficiently stiff and strong to support physiological loads. Factors impairing this process are expected to compromise strength and increase fracture risk. We tested the hypotheses that individuals with reduced stiffness relative to body size will show an increased risk of fracturing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 37 publications
(53 reference statements)
8
56
0
Order By: Relevance
“…Bone tissue is brittle in narrower tibia, supporting the notion that increased Ct.Dn is a compensatory mechanism for a structurally weaker bone, as shown in male cadaveric specimens [50], in vivo in women [37], and in stress fracture cases [51,52]. In support of these previous findings, volumetric Ct.Dn was inversely related to periosteal (and endosteal) perimeter at Baseline, indicating that those with lower crosssectional area had higher Ct.Dn.…”
Section: Discussionsupporting
confidence: 74%
“…Bone tissue is brittle in narrower tibia, supporting the notion that increased Ct.Dn is a compensatory mechanism for a structurally weaker bone, as shown in male cadaveric specimens [50], in vivo in women [37], and in stress fracture cases [51,52]. In support of these previous findings, volumetric Ct.Dn was inversely related to periosteal (and endosteal) perimeter at Baseline, indicating that those with lower crosssectional area had higher Ct.Dn.…”
Section: Discussionsupporting
confidence: 74%
“…Previously, we showed that men and women of both ethnicities demonstrated natural variation in the manner to which robustness, cortical area, and tissue mineral density are associated with one another across long bones [11,12,20,21]. Slender bones are 30% to 180% less stiff and strong than robust bones, relative to body size, with a lower bone strength index, narrower diameter, and lower cortical area [20].…”
Section: Discussionmentioning
confidence: 98%
“…Thus, there would appear to be a biological constraint in the level to which cellular processes (eg, osteoclastic/osteoblastic-driven modeling and remodeling) can be adjusted to mechanically compensate for the natural variation in robustness. It is well known that women tend to have more slender bones than men for a given body size [1,18,19,22], putting them at greater risk of fracturing under extreme loading conditions (eg, military training and falls among the elderly) [1,11,12,17]. However, it had yet to be determined whether this difference in strength is the result of fundamental differences in the manner by which men and women construct bone.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from the present study indicated that recruits with narrower tibiae were at a greater risk of stress fracture, independent of body size. A slender tibia has previously been identified as a risk factor for stress fracture in male military recruits [7,8,31]. There is some evidence that bone attempts to compensate for this functional inequivalence by increased bone mineralisation [32].…”
Section: Dxamentioning
confidence: 98%